K2: Background Survey – the search for undiscovered transients in Kepler/K2 data. Issue 1 (6th August 2020) - Ridden-Harper, R; Tucker, B E; Gully-Santiago, M; Barentsen, G; Rest, A; Garnavich, P; Shaya, E
ABSTRACT: The K2 mission of the Kepler Space Telescope offers a unique possibility to examine sources of both Galactic and extragalactic origin with high-cadence photometry. Alongside the multitude of supernovae and quasars detected within targeted galaxies, it is likely that Kepler has serendipitously observed many transients throughout K2 . Such events will likely have occurred in background pixels, coincidentally surrounding science targets. Analysing the background pixels presents the possibility to conduct a high-cadence survey with areas of a few square degrees per campaign. We demonstrate the capacity to independently recover key K2 transients such as KSN 2015K and SN 2018oh. With this survey, we expect to detect numerous transients and determine the first comprehensive rates for transients with lifetimes of ≤1 d.